A Comparative Study of Exclusive Breastfeeding Practices Among Working and Non-Working Women in Bharatpur-Tandi, Chitwan, Nepal - Duwadi, Sabina; Upadhyay, Hari Prasad (Nepalese Journal of Statistics, 2018)
Background: Breastfeeding has been accepted as the most vital intervention for reducing infant mortality, ensuring optimal growth and development of children. Twenty-two percent of newborn deaths can be prevented through breastfeeding in the first hour of birth. Objective: The objective is to find the proportion of exclusive breastfeeding practices among working and non-working women and significant factors associated with exclusive breastfeeding practices. Exclusive breastfeeding means a baby receives only breast milk without any additional food or drinks, including water until 6 months of age. Materials and Methods: Semi-structured schedule was adopted to take the information from the respondents. The sample size of the study was 140 of which 70 working and 70 non-working women were selected purposively. Results: The percentage of exclusive breastfeeding practices among working women was 67.10% and 81.4% among non-working women. More than 90% of the women knew the importance of breastfeeding. Similarly, 68.9% of working and 67.7 % of the non-working women had initiated breastfeeding within one hour of birth. Type of family, number of children, working hour were statistically significant to exclusive breastfeeding practices. Conclusion: Exclusive breastfeeding practices were quite higher among non-working women compared to working women. In order to improve breastfeeding practices the concerned authority should formulate the provision of child health care center at working places. Nepalese Journal of Statistics, Vol. 2, 1-10